Multifunctional PLA/PHA-Based films incorporating Moluccella spinosa extract for sustainable and antimicrobial food packaging applications - Pekdemir, Sibel Selcuk; Gurler, Nedim; Sancar, Pelin Yilmaz; Karagulle, Burcu; Kok, Mediha; Pekdemir, Mustafa Ersin; Qader, Ibrahim Nazem (Springer, 2026)
In this study, a novel plant-based shape memory biocomposite was developed for sustainable food packaging applications. A poly(lactic acid)/poly(hydroxyalkanoate) (PLA/PHA) blend was reinforced with the ethanolic extract of Moluccella spinosa, a plant recognized for its bioactive constituents. Structural and thermal analyses confirmed the successful incorporation of the extract without compromising the polymer matrix integrity. The results demonstrated improved barrier performance, characterized by lower water vapor permeability, reduced moisture content, and slightly increased opacity with increasing concentrations of M. spinosa extract. In addition, the composite films exhibited enhanced shape memory behavior, which became more pronounced at higher extract concentrations. Antimicrobial assays revealed a limited and selective inhibitory effect, primarily against Gram-positive bacteria (Enterococcus faecalis and Clostridium perfringens), while no notable activity was observed against Escherichia coli and Staphylococcus aureus. These findings indicate a preliminary antimicrobial potential, likely associated with a sustained-release mechanism rather than strong bactericidal activity. Overall, the integration of M. spinosa extract into the PLA/PHA matrix offers a promising route to design multifunctional, biodegradable packaging materials with shape memory capability, where antimicrobial functionality serves as a complementary feature, contributing to the advancement of environmentally friendly and active food packaging technologies.
Keywords: Poly lactic acid; M. spinosa; Food packaging; Shape memory polymer; Antimicrobial activity